Worldwide Survey of COVID-19–Associated Arrhythmias. (7th February 2021) - Coromilas, Ellie J.; Kochav, Stephanie; Goldenthal, Isaac; Biviano, Angelo; Garan, Hasan; Goldbarg, Seth; Kim, Joon-Hyuk; Yeo, Ilhwan; Tracy, Cynthia; Ayanian, Shant; Akar, Joseph; Singh, Avinainder; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Coronavirus disease 2019 (COVID-19) has led to over 1 million deaths worldwide and has been associated with cardiac complications including cardiac arrhythmias. The incidence and pathophysiology of these manifestations remain elusive. In this worldwide survey of patients hospitalized with COVID-19 who developed cardiac arrhythmias, we describe clinical characteristics associated with various arrhythmias, as well as global differences in modulations of routine electrophysiology practice during the pandemic. Methods: We conducted a retrospective analysis of patients hospitalized with COVID-19 infection worldwide with and without incident cardiac arrhythmias. Patients with documented atrial fibrillation, atrial flutter, supraventricular tachycardia, nonsustained or sustained ventricular tachycardia, ventricular fibrillation, atrioventricular block, or marked sinus bradycardia (heart rate<40 bpm) were classified as having arrhythmia. Deidentified data was provided by each institution and analyzed. Results: Data were collected for 4526 patients across 4 continents and 12 countries, 827 of whom had an arrhythmia. Cardiac comorbidities were common in patients with arrhythmia: 69% had hypertension, 42% diabetes, 30% had heart failure, and 24% had coronary artery disease. Most had no prior history of arrhythmia. Of those who did develop an arrhythmia, the majority (81.8%) developed atrial arrhythmias, 20.7% developed ventricular arrhythmias, and 22.6% had bradyarrhythmia. Regional differences suggested a lower incidence of atrial fibrillation in Asia compared with other continents (34% versus 63%). Most patients in North America and Europe received hydroxychloroquine, although the frequency of hydroxychloroquine therapy was constant across arrhythmia types. Forty-three percent of patients who developed arrhythmia were mechanically ventilated and 51% survived to hospital discharge. Many institutions reported drastic decreases in electrophysiology procedures performed. Conclusions: Cardiac arrhythmias are common and associated with high morbidity and mortality among patients hospitalized with COVID-19 infection. There were significant regional variations in the types of arrhythmias and treatment approaches.